Effect of service quality against visitor loyalty through visitor satisfaction - Hidayat, Firman; Asnawi, Nur (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
The success of a government intention is to the satisfaction of the community about the service provided by the intense, the quality of service, satisfaction, and validity are important aspects that must be considered so that government institutions can be considered successful in serving the community. The purpose of this study was to determine the direct effect of service quality on visitor satisfaction and visitor loyalty and the influence of visitor satisfaction on visitor loyalty and the influence of service quality on visitor loyalty through visitor satisfaction. From this background this research was carried out with the title